The answer is (x - 7) (x + 3) = 0
Explanation: Put both equations equal to 0, so it looks like this: (x - 7) = 0 (x + 3) = 0
It doesn’t matter what you do first but I’ll start with (x - 7) = 0
First you remove the parenthesis
x - 7 = 0
Next you add the 7 on both sides. You do this to cancel the 7 so that the x is by itself.
x = 7
It’s the same thing for the (x + 3) = 0 but I’ll show you anyways
Remove parentheses
x + 3 = 0
Subtract the 3 from both sides that way the 3 cancels out and the x is on its own
x = -3